Glyphosate Contamination at Several Concentrations And Its Impact on Changes in Goat (Capra hircus) Organ Tissue - Ali Harokan; Totong Kamaluddin; Daniel Saputra; Nurhayati Damiri (Research Centre of Inorganic Materials and Complexs, 2021)
Herbicides are generally used in the control of weeds in plants. The use of synthetic chemicals such as herbicides is known to have a negative impact on the environment. This is because the chemicals in the herbicide can kill or poison the organisms that eat plants that are exposed to these chemicals. Glyphosate is one of the active ingredients of herbicides which is systemic, so it may leave a residue on weeds such as grasses which are usually used as animal feed. The aim of this study is to analyze the impact of glyphosate residues on changes in the organ tissue of goats (Capra hircus) fed with feed exposed to glyphosate compounds. The study was conducted using an experimental method with four treatments of glyphosate concentration including control. The treatment consists of four goats with age of 12 months. The results showed that glyphosate treatment in feed influenced the development and tissue of the goats. The higher the concentration of the residue exposed to the feed, the higher the residual concentration of glyphosate in livestock blood, namely 0.2377 ppm (P1), 0.3118 ppm (P2), and 0.9377 ppm (P3), respectively. The results of the observation on livestock organ tissue showed that there was severe damage to the liver and minor damage to the lung, gastric and kidney tissue. The higher the concentration of the residue exposed to the feed, the higher the residual concentration of glyphosate in livestock blood and causing more damage.